Pembuatan Briket dari Tongkol Jagung sebagai Solusi Energi Terbarukan di Desa Margomulyo - Elsa Nuraprilia; Lailatul Mukaromah; Wasiifatul Jannah; Diva Salsabila Zahrani (Lembaga Pengembangan Kinerja Dosen, 2024)
Agricultural waste, when managed properly, is not merely production residue but also holds significant economic potential. Margomulyo Village, as a major corn-producing center, has abundant corn waste. To address the waste problem and simultaneously boost the village's economy, the production of corn briquettes is an attractive alternative. Corn briquettes, as a biomass-based alternative fuel, are rich in carbon content and can be utilized as a clean energy source.